Accounting and Reporting for Not-for-Profit Organizations - Galasso, Melisa F. (Aicpa Ser., 2020)
This title provides the tools necessary to go beyond the theory and create value-added services for accountants' clients. In the not-for-profit arena. This book allows readers to examine, evaluate, and perform case studies, which will enhance their working knowledge of fundamental not-for-profit accounting and reporting, presentation requirements, note disclosures unique to not-for-profits, and options allowed under generally accepted accounting principles. Key topics include: -Financial statement presentation, including FASB's financial reporting standard -Statement of activities -Statement of financial position and statement of cash flow -Note disclosures -Contribution concepts -Functional expense and allocation of costs -Endowments -Operating versus non-operating -Split interest agreements and beneficial trusts -Agency transactions -Programmatic investments -Common financial statement mistakes.